Intra-axonal protein synthesis - a new target for neural repair? - Jeffery L Twiss; Ashley L Kalinski; Rahul Sachdeva; John D Houle (Neural Regeneration Research, 2016)
Although initially argued to be a feature of immature neurons with incomplete polarization, there is clear evidence that neurons in the peripheral nervous system retain the capacity for intra-axonal protein synthesis well into adulthood. This localized protein synthesis has been shown to contribute to injury signaling and axon regeneration in peripheral nerves. Recent works point to potential for protein synthesis in axons of the vertebrate central nervous system. mRNAs and protein synthesis machinery have now been documented in lamprey, mouse, and rat spinal cord axons. Intra-axonal protein synthesis appears to be activated in adult vertebrate spinal cord axons when they are regeneration-competent. Rat spinal cord axons regenerating into a peripheral nerve graft contain mRNAs and markers of activated translational machinery. Indeed, levels of some growth-associated mRNAs in these spinal cord axons are comparable to the regenerating sciatic nerve. Markers of active translation tend to decrease when these axons stop growing, but can be reactivated by a second axotomy. These emerging observations raise the possibility that mRNA transport into and translation within axons could be targeted to facilitate regeneration in both the peripheral and central nervous systems.